Occurrence of Ochratoxin A in the Wild Boar (Sus scrofa): Chemical and Histological Analysis - Bozzo, Giancarlo (MDPI, 2012)
Ochratoxins are fungal secondary metabolites that may contaminate a broad variety of foodstuffs, such as grains, vegetables, coffee, dried fruits, beer, wine and meats. Ochratoxins are nephrotoxins, carcinogens, teratogens and immunotoxins in rats and are also likely to be in humans. In 2009/2010, a survey of the presence of Ochratoxin A (OTA) in regularly hunted wild boars in the Calabria region of southern Italy detected OTA in 23 animals in the kidney, urinary bladder, liver and muscles: 1.1 ± 1.15, 0.6 ± 0.58, 0.5 ± 0.54 and 0.3 ± 0.26 μg/kg, respectively. Twelve tissue samples showed levels of OTA higher than the guideline level (1 μg/kg) established by the Italian Ministry of Health. In five wild boars, gross-microscopic lesions were described for the organs displaying the highest concentrations of OTA determined by HPLC-FLD analysis, i.e., the kidney, liver and urinary bladder.